KENDAL CITY BRANDING - Ismiati, Dwi; Rachman, Anung; Setiawan, Aris (Jurnal Bahasa Rupa, 2023)
In 2021, Kendal district launched the city branding program through Kendal Handal "Beautiful Land Good Bussines". This research aims to describe and analyze meaning of symbols contained in Kendal logo. Logo is a symbol represents person and used to visualize the image or characteristic institution, company or organization. This research uses qualitative method with theory iconography and iconology by Erwin Panofsky to reveal meaning of logo through the aesthetic aspects of design. Through a semiotic approach by Charles Sanders Peirce to examine in depth elements of meaning in Kendal logo. Based on the findings of analysis, Kendal logo able to carry local wisdom values that characterize regional uniqueness. Visual element Kendal logo shown from use of colors, variety icons and visual stylization structure that radiates and spreads. An important findings this research that conceptually Kendal logo does not imply a logo that looks simpler. The signs on elements Kendal logo in line with vision and mission of Kendal government, to become leading industrial and tourism center. The meaning shape logo is not something static, surely will be change according to conditions inside. Kendal logo is part existing dynamics and represents geographical, historical and cultural conditions in every era.